Analisis Metode MOORA dan MOOSRA Dalam Pemilihan Peserta Olimpiade Matematika - Paska Miranda Sitanggang; Mesran; Kristian Siregar (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2022)
The mathematics olympiad is one of the prestigious events in education where the winners of the competition are talented and selected people with above average intelligence, the olympiad winners also affect the good name of the educational institution where the participants of the competition get education. This makes it important in selecting participants who will be sent to take part in the competitions that have been held in order to minimize the possibility of things that are not wanted to happen. Selection was made using the help of a decision support system to help make it easier to select and select candidates subjectively and accurately, in this study we will look at the work of the Moora and Moosra methods in helping the selection of participants in the mathematics olympiad at SMP N 2 Pangururan.